Debit Cards for Local Community’s Monetary Transactions: A Literature Review - Rozzani, Nabilah; Mohamed, Intan Salwani; Syed Yusuf, Sharifah Norzehan (Asian Journal of Accounting Perspectives, 2015)
This conceptual paper provides a review of past studies that highlight the development of debit cards in society. A review of past literature was conducted, in which the issues were highlighted and recommendations for potential solutions for an improvement in the usage of these debit cards in a community were discussed. This paper highlights issues in the usage of debit cards for a local community. The review reveals that despite the encouraging adaptation of debit cards in the overall world economy, there are still some loopholes that need to be covered. Hence, several remedies, including intensive promotion to the public, are needed, especially if the card is being introduced as a mechanism for transactions in a particular community.